Growth Response of Brachystegia longifolia to Copper Mining Pollution-Induced Heavy Metal Toxicity - Mulenga, Charles (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD) -- Stellenbosch University, 2022.